2011
DOI: 10.1111/j.1533-2500.2011.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Meralgia Paresthetica with Ultrasound‐Guided Pulsed Radiofrequency Ablation of the Lateral Femoral Cutaneous Nerve

Abstract: A 23-year-old female with an 18-month history of left anterolateral thigh paresthesias and burning pain consistent with meralgia paresthetica was referred to our clinic after failing trials of physical therapy, nonsteroidal anti-inflammatories, gabapentin, and amitriptyline. We performed 3 lateral femoral cutaneous nerve blocks with corticosteroid over a 4-month period; however, each block provided only temporary relief. As this pain was limiting the patient's ability to perform her functions as an active duty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 33 publications
0
21
0
2
Order By: Relevance
“…To date, few studies have assessed the ability of US to guide treatment of subcutaneous nerve injuries. In their case report, Fowler et al described the treatment of meralgia paresthetica with US‐guided pulsed radiofrequency ablation of the lateral femoral cutaneous nerve. In a further single case study, Rhame et al reported the use of cryotherapy under US guidance in treating refractory sural neuroma.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…To date, few studies have assessed the ability of US to guide treatment of subcutaneous nerve injuries. In their case report, Fowler et al described the treatment of meralgia paresthetica with US‐guided pulsed radiofrequency ablation of the lateral femoral cutaneous nerve. In a further single case study, Rhame et al reported the use of cryotherapy under US guidance in treating refractory sural neuroma.…”
Section: Discussionmentioning
confidence: 85%
“…Good visibility of subcutaneous nerves and associated neuromas may help pave the way for US‐guided percutaneous procedures, such as the ones used in patients with deeper and sensorimotor nerve stump syndrome, Morton neuroma, meralgia paresthetica, and carpal and tarsal tunnel syndromes. Phenol injection, alcohol ablation, corticosteroid injection, pulsed radiofrequency treatment, extracorporeal shock wave therapy, and cryoprobe treatment (cryoablation and cryoneurolysis) have been used with varying success rates. To date, few studies have assessed the ability of US to guide treatment of subcutaneous nerve injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of this report, that the LFC crossing over the ASIS and iliac crest can be a clinical problem, has been noted recently in a woman whose nerve was observed on ultrasound to be markedly flattened and over the crest on the symptomatic side while in a position deep to the inguinal ligament on the asymptomatic side (Park, Kim, Hwang, & Bun, ). Ultrasound identification of the LFC has been well‐described (Bodner et al, ; Zhu et al, ), is usually used for guided nerve blocks (Hara, Sakura, & Shido, ; Vandebroek, Vertommen, & Huyghe, ), but has also been reported related to diagnosis of LFC entrapment (Aravindakannan, ; Fowler & Tucker, ).…”
Section: Discussionmentioning
confidence: 99%
“…[31] Fowler et al performed US guided PRF (42°C, 2x120 second) in a patient diagnosed with Meralgia Paresthetica who was unresponsive to various treatments. [32] They reported excellent pain relief in controls at 1.5 th and 3 rd month. Authors report US provides great convenience in identification of LFCN.…”
Section: Genitofemoral Nerve Blockadementioning
confidence: 94%